LEGAL ANALYSIS OF THE APPLICATION OF THE CONCEPT OF ‘HUMAN SECURITY’ IN IMMIGRATION POLICY TO COMBAT HUMAN TRAFFICKING IN INDONESIA (A RESEARCH STUDY AT THE CLASS I SPECIAL IMMIGRATION OFFICE IN BATAM) - Randy Asmoro Dwi Purnomo; Ramlan; Dahlan; Erniyanti (CV. RADJA PUBLIKA, 2025)
Human Trafficking (TPPO) is a complex and evolving transnational crime, particularly in border areas such as Batam City, which serves as a strategic route for cross-border human movement. Combating TPPO requires not only a repressive legal approach but also a human security-based protection approach that places individuals at the center of protection efforts. This study aims to analyze from a legal perspective how the concept of human security is applied in Indonesian immigration policy to combat TPPO, with a specific focus on the Batam Class I Special Immigration Office. The research methods used are normative legal methods and empirical legal methods with a statutory and sociolegal approach. Data were obtained through literature studies, legal documentation, and interviews with immigration officials and relevant agencies in Batam. The results of the study indicate that existing laws and regulations, such as Law Number 6 of 2011 concerning Immigration and Law Number 21 of 2007 concerning the Eradication of TPPO, have provided an adequate legal basis. However, the implementation of the human security concept in immigration policy has not been optimal due to overlapping regulations, weak inter-agency coordination, technological limitations, and officials' lack of understanding of human security principles. The Batam TPI Immigration Office has attempted to implement preventive and repressive measures, but still requires increased institutional capacity and inter-agency synergy. Recommendations include the development of integrated operational guidelines based on human security, training immigration officers, strengthening early detection systems and inter-agency coordination, and increasing the state's role in ensuring comprehensive legal protection for victims of human trafficking.